Local chromatic correction optics for Future Circular Collider e^{+}e^{−} - Pantaleo Raimondi; Simone Maria Liuzzo; Laurent Farvacque; Simon White; Michael Hofer (Physical Review Accelerators and Beams)
Local chromatic correction optics are proposed for the Future Circular e^{+}−e^{−} Collider. These new optics assume an identical layout of the magnets at all operation energies and include a new design for the arcs, for the straight sections, and for the final focus. The arcs design is a step forward from the classic FODO lattice that achieves near cancellation up to the fourth order of chromatic and geometric aberrations. Straight sections and the final focus benefit from the application of transparency conditions and are thus minimally impacting the global beam dynamics. The final focus design includes both vertical and horizontal chromaticity correction sections, crab sextupoles, and additional specific sextupoles and decapoles for the optimization of the dynamics off-energy. Decapoles are very effective in mitigating the reduction of dynamic aperture due to synchrotron radiation. Nonlinear magnet settings are further optimized with multiobjective algorithms. The overall properties of the new optics proposed are analyzed in the presence of errors and compared to other optics designs.